Comprehending Suicide: Landmarks in 20th–century Suicidology.
DOI: 10.1037/10406-003
|View full text |Cite
|
Sign up to set email alerts
|

Suicide: A study in sociology.

Abstract: In the 18th and 19th centuries, the notions of political arithmetic, of statistics, of the symmetry and power of numbers were in the air. In 1741, the science of statistics as it is known today came into existence with the work of Sussmilch, a Prussian clergyman who made a systematic attempt to correlate "political arithmetic," or what we now call "vital statistics." ("Statistics" referred to the "istics" of the state.) From this study came what was subsequently called the "laws of large numbers," which permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

77
2,089
7
85

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,080 publications
(2,258 citation statements)
references
References 0 publications
77
2,089
7
85
Order By: Relevance
“…Shneidman [6] lists two types of suicide closely associated with relationship problems, which are: 'thwarted love and belonging' and 'failed relationship'. Additionally, some similarities can be spotted between the present region and Durkheim's [4] anomic suicide which, as explicated by the researcher, is triggered by overwhelming changes in one's life, e.g. the loss of a loved one.…”
Section: Themes In Genuine and Simulated Suicide Notesmentioning
confidence: 84%
“…Shneidman [6] lists two types of suicide closely associated with relationship problems, which are: 'thwarted love and belonging' and 'failed relationship'. Additionally, some similarities can be spotted between the present region and Durkheim's [4] anomic suicide which, as explicated by the researcher, is triggered by overwhelming changes in one's life, e.g. the loss of a loved one.…”
Section: Themes In Genuine and Simulated Suicide Notesmentioning
confidence: 84%
“…The seminal work of Durkheim (1951) was the first to analyze suicide in the 19th century from the viewpoint of social science. According to Durkheim (1951), suicide is a predictable consequence of the degree to which one is integrated into society.…”
Section: Introductionmentioning
confidence: 99%
“…According to Durkheim (1951), suicide is a predictable consequence of the degree to which one is integrated into society. Hence, the relation between individuals and society should be analyzed when we explore how and why individuals commit suicide.…”
Section: Introductionmentioning
confidence: 99%
“…One of the central components of de Catanzaro's theory is that individuals will engage in suicidal ideation and behavior if they become a burden to their families to prioritize the needs of the family. A similar view of suicide was originally advanced by Durkheim (1897Durkheim ( , 1951, who suggested that some individuals will commit "altruistic" suicide to benefit others. In this context, risk factors such as physical illness, depression, and job loss may be associated with suicidal tendencies because they are also associated with circumstances in which individuals desire to relieve the burden placed on family members.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 81%